How to reach true sustainable development: Green growth or steady state ecomnomics? - Kvarving, Lake (Universitetet i Nordland, 2013)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2013 This thesis will highlight the main differences between green growth and steady state economics to determine which school of thought is better apt in achieving environmental, economic and cultural sustainable development. These findings will be used to clarify what sustainable development is and to find what factors are essential in achieving it. How can businesses today ensure sustainable development and by what means can this be achieved? This will be exemplified by studying the Sahara Forest Project (SFP), a Norwegian limited liability company aimed at achieving true sustainable development. I reveal which school of thought the company most resembles, what factors have been or must be considered and in what way can they change business and production processes to best achieve sustainable development. The methodology used in this thesis is a combination of hermeneutical science and literature studies. The empirical data is collected from literature found on the SFP’s website and from company brochures. I found 3 factors to be essential in achieving true sustainable development. The first factor is a company’s preanalytic vision of the economy. The second essential factor is determining if the company operates within the boundaries of strong or weak sustainability and the third factor depends on what image of man the company has established. The SFP shared a similar preanayltic vision of the economy and image of man to that of steady state economics. I was unable to determine if the company operated within the boundaries of strong or weak sustainability. The main conclusion is that the Sahara Forest Project has yet to prove it is achieving true economic, environmental or cultural sustainability. This cannot be determined until it gives the general public full access to its accounting records.